Demographic Factors and Medical School Experiences Associated with Students' Intention to Pursue Orthopaedic Surgery and Practice in Underserved Areas. Issue 1 (19th January 2023) - Cerasani, Michele; Omoruan, Moje; Rieber, Carolyn; Nguyen, Mytien; Mason, Hyacinth R.C.; Clair, Brian; Stain, Steven C.; Mason, Amadeus R.; Levin, L Scott
Abstract : Introduction: Physician shortages across the United States will affect access to orthopaedic care for patients. Orthopaedic surgery is predicted to have one of the largest shortages among surgical subspecialties by 2025, which will disproportionally affect patients in medically underserved areas. This study examines characteristics and experiences of graduating medical students interested in orthopaedic surgery who intend to practice in underserved areas (IPUAs). Methods: We analyzed deidentified data of AAMC Graduation Questionnaire respondents who matriculated between 2007 to 2008 and 2011 to 2012. Forty-eight thousand ninety-six (83.91%) had complete demographic, financial, and medical school elective data and were included in the study cohort. Multivariable logistic regression was performed to determine the correlation between student characteristics and intention to pursue orthopaedic surgery and IPUAs. Results: Of the 48, 096 students with complete information, 2, 517 (5.2%) intended to pursue a career in orthopaedic surgery. Among the orthopaedic students, men were less likely than women to report IPUAs (adjusted odds ratio [aOR], 0.6; 95% CI, 0.4-0.8). Students who identified as Black/African American (aOR, 5.0; 95% CI, 3.0-8.2) or Hispanic (aOR, 2.0; 95% CI, 1.1-3.5) were more likely than White students to report IPUAs. Medical students who intend to pursue orthopaedics and received a scholarship (aOR, 1.5; 95% CI, 1.1-2.0), participated in community research (aOR, 1.8; 95% CI, 1.4-2.3), or had a global health experience (aOR, 1.9; 95% CI, 1.5-2.5) were more likely to report IPUAs. Discussion: If orthopaedic surgeons who reported as medical students who reported IPUAs actually do so, recruiting and retaining more sex and race/ethnically diverse orthopaedic surgeons could reduce the impact of the impending shortage of orthopaedic surgeons in underserved areas. IPUA is correlated to medical school experiences related to cultural competency including global health experiences and community-based research projects.